Higher Education and Technological Disruption: Purpose, Structure and Financing - Heywood, John (My University, 2017)
Pragmatic decisions arising from arguments about the financing of higher education and the merits of student loans are likely to lead to step by step changes in present models of higher education which maintain a continuity with the past. It seems to be generally accepted that computer assisted learning will play a greater role than in the past, however there are also likely to be changes in the structure of programmes. For example, in the U.K. many present three year degree programmes are likely to be compressed into two years, and in the U.S some commentators argue that the community colleges will have to be revitalized. Characteristic of these developments will be their continuity with the past. In this scenario workforce forecasting will continue to be governed by perceptions that STEM graduates are in short supply. The curriculum will remain largely as it is, and the utilitarian philosophy that governs higher education will continue to value some subjects, particularly those that lead to higher earnings, over others especially those where the graduate premium is negative. Attempts to move students into more vocational courses are unlikely to succeed because of the low status they are perceived to have. On the one hand this report has concerns itself with the ever increasing costs of higher education. Student loans are justified by a utilitarian philosophy that treats students and workers as commodities. Since there is a considerable differential between graduate and non-graduate earnings undergraduates should contribute to the costs of their education. These have increased considerably in the last decade, and contributed to rising inequalities. It is argued that the present system is untenable. It is noted that suggestions have been made for changing the structure of higher education programmes so as to reduce the costs. On the other hand this report also concerns itself with impact of changing technologies on the workforce and in consequence higher education. It is argued that there is now a need to take “permanent” (continuing) education seriously and to view it as part of a system that begins in elementary school. The weaknesses of a purely utilitarian education are exposed and a case, based on the needs of both industry and society, for a basic higher education that is liberal is presented. Policy makers have to be persuaded that a utilitarian education that solely serves the economy is unbalanced. The “self” and “society” are of equal importance. A structure that combines a basic higher education with a “permanent” system of continuing education is proposed in which the basic higher education is funded by the state and the “permanent” education by the individual. It is suggested that individuals might provide that funding through dedicated insurance.
Keywords: Higher Education, Artificial Intelligence, Labour Market